The Spillover Mechanisms Linking Family Conflicts and Juvenile Delinquency Among Chinese Adolescents - Liu, Tzu-Hsuan (International journal of offender therapy and comparative criminology, 2020)
The mechanisms through which conflicting parental relationship and parenting practices influence adolescent antisocial behavior have not been adequately understood. To bring more understanding to the mechanisms, this study investigates how marital discord interrelates with interparental inconsistency in parenting practices, and how these family conditions influence juvenile delinquency through their spillover effects on mental health problems, parental attachment and delinquent peer association among Chinese adolescents. Findings obtained from a structural equation modeling analysis of survey data collected from a probability sample of 2,496 adolescents (mean age = 15.16 years) are generally consistent with the spillover effect hypothesis. The results demonstrate that mental health problems, parental attachment, and delinquent peer association operate as critical mediators linking marital discord and interparental inconsistency to juvenile delinquency.